2017
DOI: 10.1055/s-0042-124415
|View full text |Cite
|
Sign up to set email alerts
|

Lower adenoma miss rate with FUSE vs. conventional colonoscopy with proximal retroflexion: a randomized back-to-back trial

Abstract: Full-spectrum colonoscopy (FSC) promises to increase adenoma detection by providing a wider field of view. The aim of this study was to compare adenoma miss rates of FSC with those of conventional colonoscopy complemented by right-colon re-examination using scope retroflexion (CC/R). At two tertiary endoscopy facilities, patients who were scheduled for colonoscopy for the assessment of symptoms or for colorectal cancer screening/surveillance were randomized (1:1) to undergo same-day, back-to-back colonoscopies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
2
19
1
Order By: Relevance
“…This finding clearly conflicts with the results of two previous meta-analyses that reported a 19-35% reduction in overall AMR with BFTs [32,33]. However, both meta-analyses included studies that were excluded in our analysis either because they were published before 2013 [34,35], written in German [36•], and used a previous version of the Endocuff or EndoRings [37][38][39], or because they did not use CC as a comparator [40]. Similarly to the results on ADR, the Endocuff results were the most positive in these analyses.…”
Section: Discussioncontrasting
confidence: 58%
“…This finding clearly conflicts with the results of two previous meta-analyses that reported a 19-35% reduction in overall AMR with BFTs [32,33]. However, both meta-analyses included studies that were excluded in our analysis either because they were published before 2013 [34,35], written in German [36•], and used a previous version of the Endocuff or EndoRings [37][38][39], or because they did not use CC as a comparator [40]. Similarly to the results on ADR, the Endocuff results were the most positive in these analyses.…”
Section: Discussioncontrasting
confidence: 58%
“…As a matter of fact, mucosal lesions -even polypoid adenomas -can be missed, which constitute a significant risk factor for interval CRC. Adenoma miss rate (12) is cumbersome to estimate: it has been better evaluated by means of back-to-back colonoscopies under experimental settings (13,14) .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the 20 adenomas that were missed during SFV examination and detected by the Fuse were sessile (90%), diminutive (70%) and RC sited (70%). In a similar design cross over study, Papanikolaou et al[26] showed that Fuse outperformed SFV complemented by examination of the right colon with scope retroflexion regarding adenoma (10.9% vs 33.7%, P < 0.001) and polyp (3.0% vs 33.5%, P < 0.001) miss rates. The same study showed that the incremental benefit of full-spectrum colonoscopy when performed, as a second examination, was 39% higher compared to that of conventional colonoscopy with retroflexion in the cecum, regarding-adenoma miss-rate overall (Figure 2).…”
Section: Wide-angle Viewing Endoscopesmentioning
confidence: 99%
“…Incremental benefit from full-spectrum colonoscopy compared to conventional colonoscopy complemented with proximal colon examination with scope retroflexion[26]. …”
Section: Wide-angle Viewing Endoscopesmentioning
confidence: 99%